Enzymatic preparation of diacylglycerols: lipase screening, immobilization, characterization and glycerolysis performance - Xie, Rui; Peng, Xianwu; Lee, Yee-Ying; Xie, Pengkai; Tan, Chin-Ping; Wang, Yong; Zhang, Zhen (John Wiley and Sons Ltd, 2024)
Backgrounds: Glycerolysis, with its advantages of readily available raw materials, simple operation, and mild reaction conditions, is a primary method for producing diacylglycerol (DAG). However, enzymatic glycerolysis faces challenges such as high enzyme costs, low reuse efficiency, and poor stability. The study aims to develop a cost-effective immobilized enzyme by covalently binding lipase to pre-activated carriers through the selection of suitable lipases, carriers, and activating agents. The optimization is intended to improve the glycerolysis reaction for efficient DAG production.